Modeling of arterial blood flow - Azizi, Bin Ahmadi (Universiti Malaysia Sarawak (UNIMAS), 2006)
Blood flow is a study of measuring the blood pressure and finding the flow through the blood vessel. Blood flow problem has been studied for centuries where one of the motivation was to understand the condition that may contribute to high blood pressure. This occurs when the blood vessel became narrowed from the normal size.This paper presents a simple mathematical modeling of the arterial blood flow which was derived from the Navier-Stokes equations and based on some assumption. A system of nonlinear partial differential equation for blood flow and the cross-sectional area of the artery were obtained and solved numerically using two approaches which are the method of variation of parameters and a built-in function in Matlab called ODE45 which is based on Runge-Kutta. The result obtained showed that the latter method to apply for such system which is ODE45. Based on resutls that were obtained from this approach, we found that cross-sectional area does affect the blood flow in the arteries.